Certification of Pondok Pesantren as Professional Nazhir to Develop Productive Waqf - Ibrahim, Salawat Fatih (UI Scholars Hub, 2023)
Waqf is one of the potential financial instruments in Islamic economics. As a country with the largest Muslim population in the world, Indonesia has responded positively to developments in the waqf model, especially productive waqf. The waqf potential predicted in 2024 will reach 71.8 trillion, while the realization of waqf is only 199 billion. This means that there is a gap of up to 71.6 trillion between the waqf potential and its realization. This occurs as a result of the lack of knowledge about waqf, including nazhir as the manager of waqf assets. Moreover, the majority of nazirs in Indonesia is considered inexperienced, so that the management of waqf assets is only for consumption. As a vital human resource in the management of waqf, nazhir is required to have a principle of professionalism in his work, and he must understand his duties. This research is a qualitative descriptive research using literature study method. The results of this research show that the problems are caused by human resources who do not understand the functions of the nazhir profession, so certification and standardization of nazhir competencies must be implemented. As one of the nazhirs with legal entities, Pondok Pesantren can be the main target for the professional nazhir certification program. This is based on the fact that people get waqf information from religious leaders and choose to channel waqf funds through institutions that already have legality. Therefore, it is necessary to carry out certification and standardization of professional nazhir competencies so that the management of productive waqf in Indonesia is growing, especially for Pondok Pesantren because religious leaders still have a strong influence in society. Besides that, human resources of Islamic boarding school have been equipped with adequate religious knowledge in understanding waqf. Many of the Pondok Pesantren have productive waqf assets. However, it must be supported by certification so that its legality in positive law can be recognized.